Root surface and coronal caries in adults with type 2 diabetes mellitus - Hintao J, Teanpaisan R, Chongsuvivatwong V, Dahlen G, Rattarasarn C. (Blackwell Synergy, 2007)
To determine the effect of type 2 diabetes mellitus (DM) on coronal and root surface caries and to investigate some factors suspected of being related to or interacting with DM, that may be associated with coronal and root surface caries.